2014
DOI: 10.1002/ejp.516
|View full text |Cite
|
Sign up to set email alerts
|

Development and pilot test of a new set of good practice indicators for chronic cancer pain management

Abstract: Background: Pain is among the most important symptoms in terms of prevalence and cause of distress for cancer patients and their families. However, there is a lack of clearly defined measures of quality pain management to identify problems and monitor changes in improvement initiatives. Methods:We built a comprehensive set of evidence-based indicators following a four-step model: (1) review and systematization of existing guidelines to list evidence-based recommendations; (2) review and systematization of exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
0
9
0
5
Order By: Relevance
“…Se utilizó el Sistema GRADE para clasificar Evidencias y Fuerza de Recomendaciones, 18 o su equivalencia en el Sistema Unificado, 19 para seleccionar las evidencias con alta gradación (AG: A y B1) y sus respectivas recomendaciones con mayor fuerza (A, y excepcionalmente B). Este sistema, utilizado en investigaciones previas en las que se construyeron indicadores a partir de GPC, 15 es una escala consensuada para lograr una armonización en la interpretación de la evidencia, dado que diversas GPC usan sistemas de gradación diferentes.…”
Section: Selección De Recomendaciones Y Construcción De Indicadoresunclassified
“…Se utilizó el Sistema GRADE para clasificar Evidencias y Fuerza de Recomendaciones, 18 o su equivalencia en el Sistema Unificado, 19 para seleccionar las evidencias con alta gradación (AG: A y B1) y sus respectivas recomendaciones con mayor fuerza (A, y excepcionalmente B). Este sistema, utilizado en investigaciones previas en las que se construyeron indicadores a partir de GPC, 15 es una escala consensuada para lograr una armonización en la interpretación de la evidencia, dado que diversas GPC usan sistemas de gradación diferentes.…”
Section: Selección De Recomendaciones Y Construcción De Indicadoresunclassified
“…In our sample, 18% of patients reported cancer pain. Pain is the symptom most commonly reported by cancer patients with treatment, and it causes major suffering to patients and their families [ 31 ]. Our findings are in agreement with those of Fischer et al [ 5 ], who found the prevalence of pain to be 20%–50% in a cancer population.…”
Section: Discussionmentioning
confidence: 99%
“…Dada la existencia de varias escalas de gradación de la evidencia y fuerza de recomendación en las GPC, se utilizó un sistema de armonización de la gradación propio. [22][23][24][25] Se seleccionaron las recomendaciones con mayor gradaje (nivel de evidencia A, fuerza de recomendación fundamentalmente A: debe hacerse).…”
Section: Búsqueda Selección Construcción Y Priorización De Indicadoresunclassified